An Improved Approach for Image Segmentation and Three-Dimensional Reconstruction - Bellaj, K.; Boujena, S.; Guarmah, E. EL (Discontinuity, Nonlinearity, and Complexity, 2026)
Themain contribution of this paper consists of introducing a novelmodel of three-dimensional reconstruction from multiple two-dimensional images. Actually, our proposedmodel presents the followingmain advantages; first, we improve the original region fitting energy in the general region-based level set method by an anisotropic diffusion to evolve the contour. Second, we use the Dijkstra algorithm to improve and allow simple and free initializations. Third, we adopt the domain decomposition method to reduce the computational cost for high-resolution images. Finally, in order to prove the efficiency and accuracy of our proposed method, experiments were performed on synthetic and real images.